Comparative analysis of nutrient and phytonutrient composition of unripe banana flour from Musa paradisiaca L. cv. ’Peyan’ and ’Monthan’ - A, Haripriya; S, Uma Mageshwari (Journal of Postharvest Technology, 2023)
Bananas and plantains are globally significant food crops, cultivated in over 130 countries. The structural, functional, and nutritional compositions of various banana cultivars exhibit considerable diversity and uniqueness. This study aimed to investigate the physical characteristics, nutrient content, phytonutrients, and antioxidant potential of two specific banana cultivars: Peyan (ABB) and Monthan (ABB). The selected bananas were in stage 1 of ripening, characterized by low total soluble solids (1.13-1.2ºBrix). The flour yield was 30.17% for Peyan and 23.25% for Monthan. The Monthan variety exhibited higher protein content compared to Peyan. Total carbohydrate content, starch, dietary fiber, and other non-starch polysaccharides were similar in both cultivars. Monthan showed considerably higher levels of flavonoids, while Peyan exhibited higher polyphenolic and tannin content. In the DPHH assay, the methanolic extracts of Peyan and Monthan recorded IC50 values of 5.006 mg/mL and 6.641 mg/mL, respectively. Unripe banana flours, with their high fiber content (13%), rich phytochemical profile, and antioxidant potential, are highly recommended for the development of functional foods.